2021
DOI: 10.1039/d0ra10159a
|View full text |Cite|
|
Sign up to set email alerts
|

Immunoassay-aptasensor for the determination of tumor-derived exosomes based on the combination of magnetic nanoparticles and hybridization chain reaction

Abstract: The detection of tumor-related exosomes is of great significance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Zhang et al, achieved lower LOD but narrow liner range compared to the proposed sensing assay. They have also employed ultracentrifugation prior to detection of EVs that lengthens the detection operation [31]. Recently published research establish that PD-L1@EVs can be used for the diagnosis of LC [28] and breast cancer [32].…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al, achieved lower LOD but narrow liner range compared to the proposed sensing assay. They have also employed ultracentrifugation prior to detection of EVs that lengthens the detection operation [31]. Recently published research establish that PD-L1@EVs can be used for the diagnosis of LC [28] and breast cancer [32].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, as such sandwich assays often require a dual-site recognition of the target, aptamers and antibodies complement each other in this manner [150]. Sandwich aptamer-antibody biosensors have been developed for different targets, such as proteins [152,154,155,[158][159][160][161][162], antibiotics [163,164], bacteria [165,166] and fungi [167,168] in various biosensing platforms. These have been recently summarized in an excellent review by Jarczewska and Malinowska [150].…”
Section: Hybrid Systemsmentioning
confidence: 99%
“…Antibody-aptamer hybrid biosensors employing HCR amplification were also reported [151,172,173]. For example, Zhang et al have applied this approach for fluorescence-assisted detection of tumorrelated exosomes [162], where the exosomes were sandwiched between CD63 antibody-functionalized magnetic nanoparticles and oligonucleotides, comprising of a PDL-1 (Programmed death-ligand 1) targeting aptamer and an initiator of HCR. In such hybrid systems, the antibody and the aptamer capture probes can be also employed simultaneously as demonstrated by Ma et al [174] for the detection of mucin 1, a cancer protein biomarker.…”
Section: Hybrid Systemsmentioning
confidence: 99%
“…[77][78][79][80][81] Owing to the flexible structure, the corresponding DNA can be ultrasensitively and homogeneously detected by previously reported DNA-based signal amplification methods, such as terminal deoxynucleotidyl transferase (TdT)-mediated polymerization and hybridization chain reaction (HCR). [82][83][84][85][86][87][88][89] For example, Gao et al reported a dual signal amplification method for indirect detection of exosomes based on the catalytic hairpin DNA cascade reaction (HDCR) and the self-assembly of DNA dendrimer on the surface of gold nanoparticles (Au NPs). 90 In this work, streptavidin (SA)-modified MBs were labeled with biotin-modified CD63 aptamer and then bound with probe S through the hybridization.…”
Section: Nanomaterials-based Optical Biosensors For Exosome Detection Fluorescence Biosensorsmentioning
confidence: 99%